2016
DOI: 10.4236/jssm.2016.93033
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Transformational Leadership and Organizational Commitment: A Study on the Bank Employees

Abstract: The purpose of this study is to determine the relationship between transformational leadership and organizational commitment. To this end, a theoretical framework regarding transformational leadership and organizational commitment was created and then an application was performed on bank employees in Kars. The results revealed relations between transformational leadership and organizational commitment. Furthermore, results regarding awareness point out an awareness in continuance commitment, which is one of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
18
2
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 12 publications
3
18
2
2
Order By: Relevance
“…The following table investigates the correlation between the independent variables and the dependent variable From the previous table, there is a significant correlation between the transformational leadership style scale and the organizational commitment dimension (the correlation value = 0.388 and, correlation is significant at the 0.01 level) in the form of a moderate inverse correlation. This finding is consistent with the studies of (Blankenship, 2010;Bushra et al 2011;Kim et al, 2012;Kathleen, 2013;Salem, 2013;Swindell, 2014;Njoroge, 2015;Rossington, 2015;Gulluce et al, 2016;Lim, 2016;Naktiyok & Yekeler, 2016;Patiar & Wang, 2016;Triana et al, 2016). Also, there is a statistically significant positive moral impact of scale effect on organizational commitment scale ideal as a whole as the test value less than0.05.…”
Section: The Relationship Between Transformational Leadership and Orgsupporting
confidence: 88%
See 2 more Smart Citations
“…The following table investigates the correlation between the independent variables and the dependent variable From the previous table, there is a significant correlation between the transformational leadership style scale and the organizational commitment dimension (the correlation value = 0.388 and, correlation is significant at the 0.01 level) in the form of a moderate inverse correlation. This finding is consistent with the studies of (Blankenship, 2010;Bushra et al 2011;Kim et al, 2012;Kathleen, 2013;Salem, 2013;Swindell, 2014;Njoroge, 2015;Rossington, 2015;Gulluce et al, 2016;Lim, 2016;Naktiyok & Yekeler, 2016;Patiar & Wang, 2016;Triana et al, 2016). Also, there is a statistically significant positive moral impact of scale effect on organizational commitment scale ideal as a whole as the test value less than0.05.…”
Section: The Relationship Between Transformational Leadership and Orgsupporting
confidence: 88%
“…The power of transformational leadership will increase employees' organizational commitment; which can be seen from the attitude of loyal employees (Bill, 2010;Kala'lembang, et al 2015). Gulluce et al (2016) clarified that a leader with transformational leadership behaviors aims to transform, encourage and inspire his/her followers for them to perform better than expected. Thus, this way of leadership leads to an increase in organizational commitment of employees.…”
Section: Transformational Leadership and Organizational Commitmentmentioning
confidence: 99%
See 1 more Smart Citation
“…This paper, which could add to the literature on the downsides of resources (see [16]) and on the downsides of leadership dimensions (see e.g., [18], for a shortcoming of transformational leadership), bridges two important gaps in the literature. First, we explore whether a classical job resource like independence at work can be potentially neutral or even harmful from a relational perspective in pairs of leaders and followers.…”
Section: Introductionmentioning
confidence: 93%
“…Many surveys show organizational commitment influenced by transformational leadership. Gulluce and Kaygin (2016) Another study said the r elationship between the leadership of transformational with organizational commitment was positive and significant Saeed et al (2013). Based on the description, it was concluded that the leadership of t ransformational have a connection with the commitment of organizational, so hypothesis 1 is: H1: Transformational leadership have a positive influence on organizational commitment…”
Section: Relationship Between Transformational Leadership and Organizmentioning
confidence: 98%